Cumulative Live Birth Rate in Patients With Thin Endometrium: A Real-World Single-Center Experience - Bu, Zhiqin; Hu, Linli; Yang, Xinhong; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Background: Studies have shown that patients with a thin endometrial thickness (EMT < 7 mm, or 8 mm) during IVF/ICSI tend to have adverse pregnancy outcomes, and this has caused much anxiety to both patients and physicians when confronted with a thin EMT. Method: From January 2015 to December 2018, patients with a thin EMT < 7 mm on the day of hCG administration during their first GnRH agonist IVF/ICSI cycle were included. According to the hysteroscopy results, patients were classified into Totally normal (Group A), Normal-with a specific abnormality (Group B), and Adhesion before transfer (Group C). Result: For the 245 patients included, approximately 60% of the thin EMT cases were the result of an intrauterine operation. CLBR was 35.45% (67/189) in this group of patients. In regard to CLBR, there were significant differences among these three uterus condition groups irrespective of the number of oocytes retrieved (28.57% versus 10.00% versus 4.76%, P=0.12 in oocyte ≤ 5; 61.36% versus 44.67% versus 23.63%, P=0.00 in oocyte > 5). In binary logistic regression analysis, age (OR=0.09, P=0.03), number of embryos available(OR=1.71, P=0.00), and uterine condition (OR=6.77, P=0.00 for Group A; OR=2.55, P=0.04 for Group B; Reference=Group C), were significantly associated with CLBR. However, EMT and endometrial pattern had no impact on CLBR. Conclusion: An intrauterine operation was the main reason for a thin EMT. Thin EMT patients with a normal uterine cavity and endometrium had a significantly better CLBR compared with those with adhesions before transfer.